2003
DOI: 10.1590/s0100-879x2003000600014
|View full text |Cite
|
Sign up to set email alerts
|

Functional changes of human quadriceps muscle injured by eccentric exercise

Abstract: The present study evaluated functional changes of quadriceps muscle after injury induced by eccentric exercise. Maximal isometric torque of quadriceps and the surface electromyography (root mean square, RMS, and median frequency, MDF) of the vastus medialis oblique (VMO) and vastus lateralis (VL) muscles were examined before, immediately after and during the first 7 days after injury. Serum creatine kinase (CK) levels and magnetic resonance imaging (MRI) were used to identify muscle injury. The subject was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 15 publications
(14 reference statements)
4
21
0
5
Order By: Relevance
“…The study concluded that VL muscle recovers a week later, and returns to its pre-exercise level at the end of the 2nd week, and was in a better level compared to its previous level (5). Similarly, in our study, muscle strength and DOMS pain reached the worst level on the 2nd day.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…The study concluded that VL muscle recovers a week later, and returns to its pre-exercise level at the end of the 2nd week, and was in a better level compared to its previous level (5). Similarly, in our study, muscle strength and DOMS pain reached the worst level on the 2nd day.…”
Section: Discussionsupporting
confidence: 77%
“…DOMS pain and loss of strength arises from damage to muscle fibers, muscle fatigue due to lactic acid and creatine kinase accumulation, degradation of connective tissue and fascia structure, muscle spasms, decrease of afferent inputs and inflammation (2,(5)(6)(7)(17)(18)(19)(20)(21). DOMS and strength loss reach their maximum value within 24-48 hours following eccentric fatigue protocol or eccentric training (2,(5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations